Proposed Integrated Marketing Strategy To Promote Brand Awareness Of Low-Waste Management - Laksmitha, Abilia; Aulia Zaim, Ilma; Kurniawan, Anton (Fakultas Ekonomi Universitas Gresik, 2023)
The waste problem is still a significant problem in Indonesia. Therefore, an applicable solution must be implemented and have a considerable impact. Simple efforts to start awareness of an environmentally friendly lifestyle can be formed by reducing everyday plastic waste, such as using refillable drinking bottles or carrying shopping bags when shopping. Various communities, organizations, and startups have emerged, contributing significantly to waste management and supporting a sustainable lifestyle. One example of a startup that has started contributing is PT Siklus Refill Indonesia. PT Siklus Refill Indonesia has contributed to reducing plastic waste by efficiently using plastic for daily household needs in the Jabodetabek area since April 2020. Since the Covid-19 pandemic, product sales have increased due to social restrictions issued by the President, so customers depend on the company to meet daily household needs. But an unexpected event befalls the company and impacts sales and customer awareness. In January 2023, the Food and Drug Supervisory Agency (BPOM) warned the company that the company is prohibited from selling household daily necessities that come in direct contact with the skin, such as shampoo, bath soap, hand washing soap, and so on. The ban was based on Food and Drug Supervisory Agency Regulation No. 12 of 2023 concerning the Supervision of the Manufacture and Distribution of Cosmetics, ratified in March 2023. This incident impacted decreasing customer brand awareness, where the company needs customer awareness to introduce new business strategies that will be issued in the third quarter. Thus, companies need integrated marketing communications to increase customer and brand awareness. The analysis in this study uses internal and external business analysis. Internal analysis used Marketing Mix (7P), VRIO, and STP analysis. Whereas for external use PESTLE, Porter's Five Forces, and stakeholder analysis. Apart from that, to support the data, the analysis was carried out by distributing questionnaires to 103 respondents to obtain the results of a consumer awareness and behavior study with various points of analysis. The results of the questionnaire analysis are processed using SPSS software and descriptive statistics that will be used to design an appropriate and effective integrated marketing communication strategy for the company